2017
DOI: 10.1007/s00127-017-1433-6
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Nepal: a modified psychological autopsy investigation from randomly selected police cases between 2013 and 2015

Abstract: Purpose Yearly, 600,000 people complete suicide in low- and middle-income countries, accounting for 75% of the world’s burden of suicide mortality. The highest regional rates are in South and East Asia. Nepal has one of the highest suicide rates in the world; however, few investigations exploring patterns surrounding both male and female suicides exist. This study used psychological autopsies to identify common factors, precipitating events, and warning signs in a diverse sample. Methods Randomly sampled fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 63 publications
6
50
1
Order By: Relevance
“…[8][9][10][11][12] However, studies which conducted psychological autopsy of complete suicides registered in the police data, have always found more number of males compared to females. 13,14 In our study sample, many individuals belonged to indigenous or disadvantaged/minority communities, and this has also been highlighted in previous studies as well. 10,12 Hence, it will be important to explore vulnerability towards suicide in these specific groups in future studies.…”
Section: Psychosocial and Personality Factorssupporting
confidence: 67%
See 1 more Smart Citation
“…[8][9][10][11][12] However, studies which conducted psychological autopsy of complete suicides registered in the police data, have always found more number of males compared to females. 13,14 In our study sample, many individuals belonged to indigenous or disadvantaged/minority communities, and this has also been highlighted in previous studies as well. 10,12 Hence, it will be important to explore vulnerability towards suicide in these specific groups in future studies.…”
Section: Psychosocial and Personality Factorssupporting
confidence: 67%
“…[8][9][10][11][12] Contrary to this, hanging has been found to be the commonest method of mortality due to suicide in Nepal. 13,14 The discrepancy in the hospital based and police data could be because hanging cases have higher fatality and these individuals are less likely survive to reach the hospitals and are more likely to be reported to the police. On the other hand, self poisoning cases in the remote regions might be under-reported to the police and mistaken for accidental cases.…”
Section: Psychosocial and Personality Factorsmentioning
confidence: 99%
“…Unfortunately, the disclosure of suicidality is rare in Nepal. Through mixed method psychological autopsies, Hagaman et al (2017) found that fewer than one-quarter of family members reported knowledge of suicidal thoughts among persons who completed suicide. This suggests the need to promote communication pathways through which persons with suicidal ideation can disclose to family, friends health workers, and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study in Nepal that included both urban and rural areas found that 16.3% of women who experienced any IPV reported a change in their mental health after the incident (Kumar et al 2012). A recent psychological autopsy study of police-reported suicides in Nepal found that at least 61% of the women who died by suicide had a relative who knew they had been physically abused as an adult (Hagaman et al 2017). Moreover, this study found that in rural Nepal the vast majority of these female suicides (85%) occurred before 26 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Because preventing adolescent suicide was a broader aim of our work in Nepal, we prioritized themes related to youth suicide and mental health. Suicide is the single leading cause of mortality among women of reproductive age [ 36 ], and in Jumla, the area where this study was conducted, 85% of suicides among women occur before the age of 25 years [ 37 ]. Work on suicide and mental health in this region of the country and elsewhere in Nepal has highlighted the importance of alcohol use, interpersonal conflict, thwarted life goals, emotional dysregulation, and lack of coping skills as risk factors [ 38 40 ].…”
Section: Methodsmentioning
confidence: 99%